Digital Halal Modules Effectiveness for Guesthouse Owners Based on Gender and Religious Background - Dimas Bayu Pinandoyo; Lu'luwatin Rosdiana Aprilia; Elviana (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
Indonesia as a Muslim-majority country still faces challenges in developing halal-friendly accommodation despite its strong position in the global Muslim-friendly tourism market. This study aims to analyze the effectiveness of a Digital Halal Modules in improving halal literacy among guesthouse owners and to explore how gender and religious background influence their perceptions and responses. A qualitative approach was employed using semi-structured interviews with five guesthouse owners in the Borobudur tourism area, Magelang, Indonesia. Data were analyzed using Reflexive Thematic Analysis supported by NVivo 12 Pro. The findings reveal that the Digital Halal Modules effectively enhances participants’ knowledge of halal principles, increases confidence in pursuing halal certification, and supports service improvement in accordance with halal standards. Although gender and religious background influence initial perceptions, they do not significantly affect the overall effectiveness of the modules. Differences were observed in motivational responses, where some participants preferred gradual implementation while others showed immediate readiness for certification. The modules was perceived as user-friendly, systematic, visually engaging, and accessible; however, limitations were identified, including dependence on internet connectivity, lack of practical examples for small-scale guesthouses, limited local contextualization, and complexity in documentation guidance. This study concludes that digital learning tools can serve as effective capacity-building instruments for micro-scale accommodation providers but require context-sensitive design to improve usability and broader adoption in halal tourism development.